Using biomarkers in patients with positive multiparametric magnetic resonance imaging: 4Kscore predicts the presence of cancer outside the index lesion. (27th September 2020) - Falagario, Ugo Giovanni; Lantz, Anna; Jambor, Ivan; Martini, Alberto; Ratnani, Parita; Wagaskar, Vinayak; Treacy, Patrick‐Julien; Veccia, Alessandro; Bravi, Carlo Andrea; Bashorun, Hafis O; Phillip, Deron; Lewis, Sara; et al.
Abstract : Objectives: To evaluate if the blood biomarker, 4Kscore, in addition to multiparametric magnetic resonance imaging information could identify patients who would benefit from undergoing only a targeted biopsy. Methods: We retrospectively analyzed a population of 256 men with positive multiparametric magnetic resonance imaging who underwent standard + targeted biopsy at Mount Sinai Hospital, New York, NY, USA. 4Kscore (OPKO Health, Miami, FL, USA) was sampled from all patients before biopsy. Uni‐ and multivariable binary logistic regression analyses were carried out to predict clinically significant prostate cancer, defined as International Society of Urological Pathology grade group ≥2, in standard biopsy cores. The model with the best area under the curve was selected and internal validation was carried out using the leave‐one‐out cross‐validation. Results: The developed model showed an area under the curve of 0.86. Carrying out only targeted biopsy in patients with a model‐derived probability <12.5% resulted in 39.5% ( n  = 101) fewer standard biopsies and a 33.9% ( n  = 20) reduction of detecting grade group 1 disease, while missing grade group ≥2 in 5.2% ( n  = 4) using standard biopsy only and 1.1% ( n  = 1) using standard biopsy + targeted biopsy. Conclusions: 4Kscore in combination with multiparametric magnetic resonance imaging can help to reduce unnecessary standard biopsy and decrease detection of clinically insignificant prostate cancer.